Point-of-Care Evaluation of Malaria Rapid Diagnostic Test (mRDT) for Detection of Plasmodium falciparum Among Children Under 5 Years of Age Attending Panyadoli Health Center III in Kiryandongo Refugee Settlement, Mid-Western Uganda - Dorcus Acan; Robert Opiro; Jacob Okot; Simon Peter Alarakol (Journal of Parasitology Research)
Conclusion: The study found comparable malaria prevalence using mRDT and microscopy. Both methods showed high Sn and Sp with moderate to strong agreement, supporting mRDT’s reliability in diagnosis. Due to its high accuracy and strong agreement with microscopy, mRDT can reliably diagnose malaria in resource-limited settings; however, confirmatory testing and periodic quality controls are recommended for accuracy and case management.